Green charged decision-making: How two-part remuneration, contract flexibility, and environmental nudging drive vehicle-to-grid participation - Meike Vey; Nils Namockel; Oliver Ruhnau (Institute of Energy Economics at the University of Cologne (EWI), 2025)
Electric mobility and renewable energy play key roles in the global energy transition. In this context, vehicle- to-grid technology, which enables bidirectional energy row between electric vehicles and the grid, could make electric vehicles usable as energy storage units, thus supporting grid stability and integration of renewable energy. However, the willingness of electric vehicle owners to participate in vehicle-to-grid contracts remains insufficiently understood, particularly regarding how they respond to speciîoc contract attributes. This paper addresses this gap by conducting a discrete choice experiment to evaluate the preferences of current and potential future German electric vehicle drivers for various vehicle-to-grid contract alternatives. We îond that cycle-based remuneration, rexible contract duration, and environmental nudging signiîocantly enhance consumer acceptance. Conversely, a lower guaranteed battery level and longer minimum plug-in durations negatively impact participation. We also test how respondent characteristics inruence participation and identify income-dependent preferences, such as lower-income individuals attributing a stronger preference to îoxed daily payments than higher-income individuals. Our differentiated îondings may be used to improve contract designs and marketing efforts to address the unique V2G preferences of various user segments.
Keywords: C25; D12; Q42; Q48; Q51; Q58; R41; 330; Vehicle-to-grid; Discrete choice experiment; Willingness to accept; Preferences; Bidirectional charging